Predictors of weight reduction effectiveness of SGLT2 inhibitors in diabetes mellitus type 2 patients - Danpanichkul, Pojsakorn; Manosroi, Worapaka; Nilsirisuk, Tharadon; Tosukhowong, Theetouch (Frontiers in Endocrinology, 2024)
Background: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are a novel medication for treating type 2 diabetes (T2DM), which have the pleiotropic effect of weight reduction.This study aimed to evaluate clinical and biochemical predictors of effective weight reduction in T2DM patients who use various types of SGLT2i.A retrospective study was conducted with 289 adults diagnosed with T2DM who were first prescribed SGLT2i either as monotherapy or add-on therapy. The primary outcome was the identification of clinical and biochemical factors that can potentially induce meaningful weight reduction (>3% in 1 year) in T2DM patients while using SGLT2 inhibitors. The relationship between predictors and significant weight loss was assessed using logistic regression analysis, including adjustment for confounding factors.Results are presented as odds ratios (ORs) with a 95% confidence interval (CI).Results: Among the 289 patients, 45.6% had significant weight loss following SGLT2i use.The significant clinical predictors were age >70 years old (OR 3.26, 95% CI 1.39-7.6, p=0.006), body mass index >25 kg/m 2 (OR 1.02, 95% CI 1.01-1.05, p=0.049), and the use of sulfonylureas (OR 2.41, 95% CI 1.15-5.09, p=0.020). Additionally, the use of HCTZ showed significantly decreased odds of weight loss (OR 0.35, p=0.043).This research highlights multiple clinical factors that potentially can predict meaningful weight loss in patients with T2DM who are treated with SGLT2i. These findings could facilitate the identification of patients who might benefit from the weight loss effects of SGLT2i.